BIRRUL WĀLIDAIN'S APPLICATIVE IN FAMILY FINANCIAL MANAGEMENT ACCORDING TO THE VIEW OF QURANIC EXEGESIS - Musthofa, Bisri; Isnaeni , Ahmad; Baihaqi, Yusuf; Makrus, Muhammad (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2023)
This study discusses the verses of birrul walidain, which are associated with family financial management and the conditioned behavior of boys toward their parents in the aspect of providing for themselves. This research departs from the problem of decreasing children's moral values towards biological parents, especially in a boy entering postmarital age. Some examples of concerning behavior from a child more likely to prioritize his support over his parents to the behavior of entrusting parents to nursing homes. This research method uses the type of library research and verse interpretation method using thematic methods. Collection of literature data by referring to the book of tafsīr with the method of tahlīlī patterned adābī ijtimāʻī, namely al-Mishbah by Quraish Shihab and Kitab tafsīr al-Azhār by Hamka. Data analysis method with interpretation method and comparative analysis. The findings in this study that birrul wālidain in family financial management are as follows: 1) parental income is prioritized 1/3 (33.3%) if they do not have children, and 1/6 (16.6%) if they already have children from their total income. 2) The wife's income is prioritized by 1/4 (25%) if she does not have children and 1/8 (12.5%) if she already has children from her total income. 3) provide for primary needs (clothing, food, and shelter) for themselves and their families (children and wives) according to the ability taken from 41.7% if they do not have children and 70.9% if they already have children from their total income. 4) provide additional income for parents or close relatives not more than 1/3 (33.3%) of their total property if they have a minimum property of 600-700 dirhams (Rp. 56,805,000-Rp. 66,272,500) or their parents have poor or infidel status even though the property does not reach 600-700 dirhams.